2021
DOI: 10.3389/fonc.2021.655709
|View full text |Cite|
|
Sign up to set email alerts
|

Identification of BRCA1:c.5470_5477del as a Founder Mutation in Chinese Ovarian Cancer Patients

Abstract: Predisposition of germline BRCA1/2 mutations (gBRCAMUT) increases the risk of breast and ovarian cancer in females, but the mutation prevalence and spectrum are highly ethnicity-specific with different recurrent mutations being reported in different populations. Hereby, we performed hybridization-based target sequencing of BRCA1/2 in 530 ovarian cancer patients from Henan, the central region of China, followed by haplotype analysis of six short tandem repeat (STR) markers in the patients with recurrent mutatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Wang et al also found that BRCA1 c.5470_5477del was highly prevalent in a population of Chinese women population [ 46 ]. Studies have shown that BRCA1 c.5470_5477del was a founder mutation in Chinese Han ovarian cancer patients [ 47 ] and Chinese Han breast cancer patients [ 48 ]. A meta-analysis conducted by Kim et al on population samples from mainland China in 2016 found that BRCA1 c.981_982delAT and BRCA2 c.3195_3198delTAAT were highly prevalent in mainland Chinese population [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wang et al also found that BRCA1 c.5470_5477del was highly prevalent in a population of Chinese women population [ 46 ]. Studies have shown that BRCA1 c.5470_5477del was a founder mutation in Chinese Han ovarian cancer patients [ 47 ] and Chinese Han breast cancer patients [ 48 ]. A meta-analysis conducted by Kim et al on population samples from mainland China in 2016 found that BRCA1 c.981_982delAT and BRCA2 c.3195_3198delTAAT were highly prevalent in mainland Chinese population [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…BRCA1 c.4065_4068del has been detected in some populations [61][62][63]. Another study showed that c.4065_4068del is one of the three most common BRCA1 variants in Chinese ovarian cancer patients [47]. In the BRCA2 gene, c.5164_5165delAG has been detected in the Chinese Han population [64], Macau population [65], and Taiwanese populations [66].…”
Section: Discussionmentioning
confidence: 99%
“…A total of 25 BRCA1 deleterious variants were detected in 29 patients, including 25 (25/29, 86.2%) protein-truncating (15 frameshift and 10 nonsense), 2 (2/29, 6.9%) missense, 1 (1/29, 3.4%) start lost, and 1 (1/29, 3.4%) E15 deletion. The most frequent variant in BRCA1 was c.5470_5477del (p.I1824Dfs*3, n = 3), which was considered a founder variant in the Chinese Han patients with BC or ovarian cancer [ 13 , 14 ]. Other recurrent BRCA1 variants were c.2998G > T (p.E1000*, n = 2) and c.228_229delinsAAAGTG (p.S76Rfs*6, n = 2).…”
Section: Resultsmentioning
confidence: 99%
“…In a large-scale cohort with 1,245 pathogenic variants identified, 48 most common pathogenic BRCA1/2 variants (39.86% of total) were not reported as common variants in Caucasians ( 15 ). The pathogenic variant BRCA1 c.5470_5477del was determined as a founder mutation in the Chinese Han population ( 25 , 26 ). Interestingly, another systematic review with 2,128 BRCA1/2 variants derived from 35,178 Chinese individuals from 23 provinces also reported that c.5470_5477del ranked as the highest frequency of all BRCA1 variants identified while the c.3109C>T ranks highest in BRCA2 ( 12 ).…”
Section: Overall Prevalence and Spectrum Of Brca M...mentioning
confidence: 99%